Analysis of bryophyte species diversity in three northeastern provinces of China and the Korean Peninsula - Yang, Chengjun; Liu, Ruiqi; Cui, Jiaqi; Wang, Hongfeng (Frontiers in Ecology and Evolution, 2025)
The three northeastern provinces and the Korean Peninsula are geographically and climatically diverse, and the geographical regions have continuously formed relatively unique flora. This paper collected through the national and provincial list of bryophytes, the specimens in the online herbarium, recently published bryophytes papers and bryophytes information recorded in field investigation in certain areas. Quantitative statistical analysis of plant species or taxa data was carried out by traditional methods. In order to clarify the species diversity and species genetic relationship of bryophytes in the study area, a preliminary study was conducted to explain the flora pattern and formation mechanism. There are 1,006 species of bryophytes belonging to 305 genera and 107 families in the three provinces of Northeast China, and there are 1,119 species of bryophytes belonging to 368 genera and 126 families in the Korean Peninsula. In addition, 477 new distribution records of bryophytes in the three northeastern provinces were supplemented. The dominant families and genera of bryophyte in the Korean Peninsula and the three northeastern provinces are highly similar, and the species richness of mosses and liverworts in the two study areas is dominated by families containing 2–10 species and single-species genera. According to a similarity analysis of family, genus and species, there are 541 species of bryophytes belonging to 269 genera and 102 families in the study area. The three northeastern provinces and the Korean Peninsula are rich in bryophytes, and are mainly distributed in temperate zones. Therefore, the similarity between Heilongjiang Province and Jilin Province in the three northeastern provinces is higher, while the similarity between Jilin Province, Liaoning Province and the Korean Peninsula is higher, indicating that the adjacent areas may have a common evolutionary origin or show evolutionary convergence. Compared with the Korean Peninsula, the proportion of tropical distribution and East Asian distribution in the three northeastern provinces is slightly higher. This study analyses the characteristics, similarity feature and floristic composition of bryophyte species and provides background information on bryophyte biodiversity conservation in the study area, which is highly important for the protection of bryophyte diversity and the promotion of basic data sharing.